2020
DOI: 10.1186/s41936-020-00177-9
|View full text |Cite
|
Sign up to set email alerts
|

Dandelion prevents liver fibrosis, inflammatory response, and oxidative stress in rats

Abstract: Background: Liver fibrosis is the main contributor to the chronic liver-associated morbidity and mortality. Purpose: The study was conducted to evaluate the effects of whole plant powder of dandelion (Taraxacum officinale) on liver fibrosis. Methods: Liver fibrosis was induced by the oral administration of 20% carbon tetrachloride (CCL4), twice a week for 8 weeks. Simultaneously, dandelion root extract (500 mg/kg) was daily administered via the same route. Results: Dandelion remarkably improved the liver histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…The total antioxidant activity, measured by the DPPH method, was 12,713.42 ± 156.41 mMT/100 g NSO and 1390.65 ± 1.45 mMT/100 g GSO. The results were in the range reported in the literature for both oils [ 25 , 26 , 27 ].…”
Section: Resultssupporting
confidence: 81%
“…The total antioxidant activity, measured by the DPPH method, was 12,713.42 ± 156.41 mMT/100 g NSO and 1390.65 ± 1.45 mMT/100 g GSO. The results were in the range reported in the literature for both oils [ 25 , 26 , 27 ].…”
Section: Resultssupporting
confidence: 81%
“…Many studies correlated the hepatoprotective activity of the medicinal plant extracts with the antioxidant compounds from these plants [ 51 ]. Moreover, other experimental studies demonstrated that the polyphenolic compounds isolated from TO extracts had a hepatoprotective effect by reducing oxidative stress through direct free radical scavenging activity, metal ions chelation, and regeneration of the membrane-bound antioxidants [ 40 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Initially a single mutated cell undergoes the promotion stage which results in the production of a tumor bulk of extremely proliferative cells. 1 Further progression of these proliferative cells lead to the development of tumor cells which undergo nonstop division that outstrip their normal counterparts. 2 , 3 A flurry of research data demonstrated the intense need to develop new strategies against these bleak realities and to investigate potential naturally derived candidates with the capability to halt these modifications and ultimately stop carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%